Biodegradable post biopsy breast marker - Teh, Wen Hui (2017)
Breast biopsy involves needle extraction of small suspicious lesion breast tissue for diagnosis. A breast marker is inserted subsequently to mark the biopsy site for future targeting and referencing due to the transition of the surrounding tissue after tissue removal and remodeling or healing of tissue around the biopsy site. Currently, metallic markers are available for post breast biopsy and they are stayed permanent should the biopsy test diagnosed as benign.